Present Status and Challenges in Cloud Monitoring Framework: A Survey - Jaber, Aws Naser; Mohamad Fadli, Zolkipli; Shahid, Anwar; Al-Hawawreh, Muna Sulieman (IEEE, 2016)
In the context of an increase in cloud computing facilities in recent years, continuous monitoring of the system plays a crucial role in enhancing the quality of cloud services. Development of suitable cloud monitoring tool is determined by the challenges faced in cloud computing environment, for example data storage, and security of on demand services. A cloud monitoring tool can provide a visually appealing, intuitive interface to allow system administrators to view network data and results, and identify problems or bottlenecks. Therefore, this article provides a review of the cloud computing tools, which are used for monitoring performance of cloud infrastructure at consumers and providers end.